Approach to activity engagement and differences in activity participation in chronic pain: A five‐day observational study. (4th September 2018) - Andrews, Nicole E.; Strong, Jenny; Meredith, Pamela J.; Branjerdporn, Grace S.
Abstract : Background/aim: Activity pacing is one of the most widely endorsed interventions used by occupational therapists to assist clients to manage chronic pain conditions. It targets two behaviours that are thought to be maladaptive: activity avoidance and overactivity (activity engagement that severely aggravates pain). However, in more recent years, the potential for activity pacing to negatively impact activity participation has been recognised which deters habitually overactive individuals from adopting the self‐management strategy. The main aim of this study was to evaluate if variances in activity participation can be explained by how individuals approach activity engagement when in pain. Methods: Sixty‐eight adults with chronic pain completed a demographic questionnaire, the Pain and Activity Relations Questionnaire (PARQ), and recorded their participation in activities for five days using a paper diary. Two of the authors independently coded the recorded activities into one of three time‐use categories: rest, productivity or leisure/social. A MANCOVA model was produced to examine differences in time use across four 'approach to activity engagement' categories which were determined by scores on the PARQ. Results: A significant multivariate effect was found. Univariate comparisons revealed that 'overactives' (high overactivity, low avoidance) and 'pacers' (low overactivity, low avoidance) spent a similar amount of time resting over the five‐day period. 'Overactives' spent the most amount of time on productive tasks and the least amount of time on social/leisure activities out of the four subgroups. Conclusion: Results suggest that activity pacing does not negatively impact on activity participation in chronic pain populations. 'Pacers' spent a similar amount of time resting, and had a slightly better balance between productive tasks and leisure/social activities, when compared to 'overactives'. The results of this study can be incorporated into patient education and highlight potential treatment avenues for individuals with chronic pain who are habitually overactive.